A highly sensitive immunosensor based on nanochannel-confined nano-gold enhanced electrochemiluminescence for procalcitonin detection - Chang, Qiang; Gu, Xinhui; He, Liming; Xi, Fengna (Frontiers in Chemistry, 2023)
Sensitive detection of procalcitonin (PCT) in serum is crucial for the timely diagnosis and treatment of rheumatoid arthritis. In this work, an electrochemiluminescence (ECL) detection platform is developed based on in-situ growth of Au nanoparticles (AuNPs) in nanochannels and an analyte-gated detection signal, which can realize ECL determination of PCT with high sensitivity. Vertically ordered mesoporous silica films with amine groups and uniform nanochannel array (NH2-VMSF) is easily grown on the supporting indium tin oxide (ITO) electrode through electrochemical assisted self-assembly method (EASA). Anchored by the amino groups, AuNPs were grown in-situ within the nanochannels to catalyze the generation of reactive oxygen species (ROS) and amplify the ECL signal of luminol. An immuno-recognitive interface is constructed on the outer surface of NH2-VMSF, through covalent immobilization of PCT antibodies. In the presence of PCT, the immunocomplex will hinder the diffusion of luminol and co-reactants, leading to a gating effect and decreased ECL signals. Based on this principle, the immunosensor can detect PCT in the range from 10 pg/mL to 100 ng mL-1 with a limit of detection (LOD) of 7 pg mL-1. The constructed immunosensor can also be used for detecting PCT in serum. The constructed sensor has advantages of simple fabrication and sensitive detection, demonstrating great potential in real sample analysis.